2014
DOI: 10.12659/msm.891102
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Abnormality in Left Nucleus Accumbens Predicts Dysfunctional Beliefs in Treatment-Resistant Obsessive-Compulsive Disorder

Abstract: BackgroundThe aim of this study was to determine whether dysfunctional beliefs might predict treatment-resistance and to examine the relationship between fractional anisotropy (FA) in diffusion tensor imaging (DTI) and cognitive biases for optimal treatment choice.Material/MethodsWe recruited 11 non-resistant obsessive-compulsive disorder (OCD) patients, 11 resistant OCD patients, and 11 healthy subjects.ResultsOCD patients had higher Obsessive Beliefs Questionnaire (OBQ-87) subscale scores than subjects in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Fan et al () found that drug treatment resulted in a reduction in radial diffusivity (RD) in the left striatum and right midbrain as well as a reduction in mean diffusivity (MD) of the right midbrain. However, an additional result showed that decreased FA values in WM of the nucleus accumbens may not be reversible by adequate treatment in OCD patients (Feng, ). The study conducted by Yoo et al () noted that WM alterations may be partly reversible with citalopram treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan et al () found that drug treatment resulted in a reduction in radial diffusivity (RD) in the left striatum and right midbrain as well as a reduction in mean diffusivity (MD) of the right midbrain. However, an additional result showed that decreased FA values in WM of the nucleus accumbens may not be reversible by adequate treatment in OCD patients (Feng, ). The study conducted by Yoo et al () noted that WM alterations may be partly reversible with citalopram treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al (2012) found that drug treatment resulted in a reduction in radial diffusivity (RD) in the left striatum and right midbrain as well as a reduction in mean diffusivity (MD) of the right midbrain. However, an additional result showed that decreased FA values in WM of the nucleus accumbens may not be reversible by adequate treatment in OCD patients (Feng, 2014) raphy study found that baseline regional cerebral blood flow in the bilateral OFC was significantly correlated with a change in clinical symptoms after CBT (Yamanishi et al, 2009). Using functional MRI, Nakao et al (2005) found that after a 12-week treatment program of CBT, the activation intensity of the orbital frontal cortex, the dorsolateral prefrontal cortex, and the anterior cingulate gyrus caused by symptoms was weakened, while the activation intensity of the temporal cortex and cerebellum increased in OCD patients.…”
Section: Changes In White Matter Microstructure In Ocd After Cbtmentioning
confidence: 99%
“…When studies reported separate results by illness subtype, these were included as separate studies, i.e. two studies with non-overlapping contrasts for BD I and BD II (Liu et al, 2010, Ha et al, 2011), one study with separate results for suicide attempters and non-attempters with MDD (Jia et al, 2010), and one study with separate results for OCD and treatment-resistant OCD (TROCD) (Li et al, 2014). The 37 VBA studies and 41 contrasts included in the meta-analysis are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Research into the role of the NAc in the context of predicting treatment outcome has been scarce, but earlier studies have linked the NAc to pharmacotherapy and psychotherapy resistance. Treatment-resistant OCD patients showed hypo-responsivity of the NAc during the anticipation of rewards ( Figee et al, 2011 ), as well as micro-structural alterations of the NAc as measured with diffusion tensor fractional anisotropy ( Li et al, 2014 ). More recently, a study investigating patients who received treatment with CBT and SSRIs for anxiety disorders found that larger baseline NAc volumes were associated with a larger reduction of anxiety symptoms ( Burkhouse et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%